Tinjauan Kehalalan Produk Kosmetika dalam Konteks Masailul Fiqhiyah di Era Modern - Khasanah, Elisa; As’ad, Ali; Mustajib, Anwar Bahrun (Jurnal El-Thawalib, 2025)
In Islam, the concept of halal and haram is the main foundation that regulates various aspects of life, including the products consumed and used. Halal cosmetics have an important role in the lives of Muslims, especially in maintaining the purity of the body and avoiding the use of materials prohibited in Islam. In this study, researchers used the library research method to examine the review of halal cosmetics in the context of masailul fiqhiyah in the modern era. In the context of cosmetics, a product is said to be halal if it does not contain ingredients that are forbidden according to Islam, such as ingredients derived from blood, pork, or alcohol, and does not cause harm to the user. Cosmetic ingredients such as alcohol, gelatin, synthetic ingredients, and animal-derived products must meet halal criteria in accordance with Islamic law. In addition, the purpose of using cosmetics must also maintain a balance between aesthetic needs and morality in Islam, avoiding vanity and extravagance. The views on halal cosmetics differ among the madhhabs. The Hanafi school is more flexible, allowing synthetic ingredients and non-khamr alcohol if they are not unclean. The Maliki and Hanbali schools are stricter, rejecting unclean ingredients, alcohol, or non-halal slaughtered animals, and prohibiting contamination with haram ingredients. The Shafi'i school emphasizes cleanliness and ensures that all materials and processes are free from haram or unclean elements. The findings show that the halalness of cosmetic products is not only determined by the raw materials used, but also the production process, packaging, and distribution. Halal certification bodies need to improve supervision and consistency in the implementation of halal standards, especially on imported raw materials and internationally marketed products. Muslim consumers are also expected to be more critical in choosing products by checking halal certification and understanding the composition of the ingredients used.